Esting of Fungal Antagonists from The Rhyzosphere of Mother-in-Law's Tongue (Sansevieria trifasciata Prain) as a Fungal Control Agent Fusarium sp. - Julianty, Dwita; Manalu, Kartika; Nasution, Rizki Amelia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Fusarium sp. is a serious problem for various plant commodities because of its ability to act as a pathogen and cause damage to plant anatomy and morphology. The rhizosphere fungus of the mother-in-law's tongue plant has more abundant inhibitory mechanisms and is able to directly inhibit hyphae growth and suppress the growth of pathogenic fungi, so it was chosen as a biocontrol agent in this research. The aim of this research was to determine the antagonistic properties and ability of the rhizosphere fungus from the mother-in-law's tongue plant (Sansevieria trifasciata Prain) against the fungus Fusarium sp. This research was carried out with data analysis starting with sterilization and making media, then taking soil samples from the rhizosphere of the mother-in-law's tongue using the purposive random sampling to continue with the isolation and purification stage of the rhizosphere fungus of the mother-in-law's tongue plant. Antagonist test of fungi from the rhizosphere of snake plant against the fungus Fusarium sp. carried out using a double culture method (dual culture). The data obtained were then analyzed using Microsoft Excel 2013 to obtain an average inhibition which shows the potential of fungi from the rhizosphere of the plants as controlling agents for the fungus Fusarium sp. The results of isolation and antagonistic tests, the five isolates of snake plant rhizosphere fungus (Sansevieria trifasciata Prain) have varying inhibitions ranging from very weak to moderate. The highest inhibition against Fusarium sp. was shown by isolate JDT12, while the lowest inhibition was shown by isolate JDT11. The antagonism mechanism found by isolate JDT12 is the antibiosis mechanism.